1013 Probability of drowning during childhood in Bangladesh. (1st September 2016) - Talab, Abu; Linnan, Michael; Rahman, Aminur; Rahman, Fazlur; Mashreky, Saidur Rahman
Abstract : Introduction: There are many drowning studies in children that have the potential to allow calculation of the risk or probability of drowning during specific periods of childhood. However, almost none of them include a nationally representative population of children and are large enough to contain enough drowning deaths to have statistical precision in estimating the per-year-of childhood risk of drowning. The Bangladesh Health and Injury Survey (BHIS) allows just such an estimate to be calculated, which puts an actual probability of drowning by year of childhood for children in Bangladesh. Methods: The mortality experience from the child sample from BHIS was examined. A life table was constructed from the child dataset which showed the probability of survival by each year of childhood according to cause of mortality. Results: 169 deaths from drowning occurred in children in BHIS. The multiple decrement life-table analysis which shows age specific probabilities of drowning for children in Bangladesh will be presented at WCDP. Conclusions: The annual risk of dying for children in Bangladesh is already known from the census and other surveys and is high compared with high income countries. The cause-specific mortality risk calculated from the BHIS survey dataset shows that drowning is the largest risk of death from a single cause to children who survive infancy in Bangladesh through their 18th birthday, when they become adults. Acknowledgements: Centre for Injury Prevention and Research Bangladesh (CIPRB)